Absence of the Genetic Marker IS6110 from a Strain of Mycobacterium tuberculosis Isolated in Ontario - Susan T Howard; Matthew T Oughton; Albert Haddad; Wendy M Johnson (Canadian Journal of Infectious Diseases)
A 35-year-old female patient from Waterloo, Ontario was diagnosed with pulmonary tuberculosis in June 1995. Records indicated that the patient had emigrated from Laos circa 1990. A culture grown from a bronchoalveolar lavage specimen was identified as Mycobacterium tuberculosis by standard biochemical methods. Drug-susceptibility testing indicated the strain was resistant to pyrazinamide (PZA), and a mutation was detected within pncA, a gene associated with PZA resistance. Sequence data from the 16S rRNA gene and the 16S/23S rRNA gene spacer confirmed that the strain was a member of the M tuberculosis complex, and analysis of the mpcA and pncA genes supported the identification of the strain as M tuberculosis rather than Mycobacterium bovis. However, the insertion element IS6110, which is used for epidemiological tracing of M tuberculosis, was not detected in this strain by either restriction fragment length polymorphism analysis or by polymerase chain reaction. Two other genetic markers associated with the M tuberculosis complex, IS1081 and the direct repeat element, were present. The arrival of immigrants with tuberculosis from southeast Asia, where most strains of M tuberculosis lacking IS6110 have been traced, has important implications for epidemiological studies of tuberculosis in North America.